Bidirectional gut-brain communication: A role for orexin-A. (December 2020) - Mediavilla, Cristina
Abstract: It is increasingly evident that bidirectional gut-brain signaling provides a communication pathway that uses neural, hormonal, and immunological routes to regulate homeostatic mechanisms such as hunger/satiety as well as emotions and inflammation. Hence, disruption of the gut-brain axis can cause numerous pathophysiologies, including obesity and intestinal inflammatory diseases. One chemical mediator in the gut-brain axis is orexin-A, given that hypothalamic orexin-A affects gastrointestinal motility and secretion, and peripheral orexin in the intestinal mucosa can modulate brain functions, making possible an orexinergic gut-brain network. It has been proposed that orexin-A acts on this axis to regulate nutritional processes, such as short-term intake, gastric acid secretion, and motor activity associated with the cephalic phase of feeding. Orexin-A has also been related to stress systems and stress responses via the hypothalamic-pituitary-adrenal axis. Recent studies on the relationship of orexin with immune system-brain communications in an animal model of colitis suggested an immunomodulatory role for orexin-A in signaling and responding to infection by reducing the production of pro-inflammatory cytokines (e.g., tumor necrosis factor α, interleukin-6, and monocyte chemoattractant protein-1). These studies suggested that orexin administration might be of potential therapeutic value in irritable bowel syndrome or chronic intestinal inflammatory diseases, in which gastrointestinal symptoms frequently coexist with behavioral disorders, including loss of appetite, anxiety, depression, and sleeping disorders. Interventions in the orexinergic system have been proposed as a therapeutic approach to these diseases and for the treatment of chemotherapeutic drug-related hyperalgesia and fatigue in cancer patients. Highlights: Orexin-A (OX-A) is a chemical mediator in the bidirectional gut-brain dialogue. Hypothalamic OX-A participates in gut secretions, motility, and nociception. Enteric OX-A transmits signals to the brain on nutritional status and inflammation. Enteric OX-A responds to infection by reducing IEB permeability and neuroinflammation. OX-A in the gut-brain axis may contribute to intestinal inflammation-related stress.